Perancangan Aplikasi Point Of Sales Pada Sumber Rejeki Jambi - Nurhadi; Oktavianus, Welsen; Eni Rohaini (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Sumber Rejeki Jambi is one of business that moves in selling material building at Jambi city where processing data still using books and counting tools. So that problems occur that is difficult to manage and counting transactions sales, the process of making the report buying and selling needs long time and occasionally there are delay, and a stock products sometimes going on with physical stock the warehouse. One of solution that make point of sales application use PHP programming language and DBMS MySQL where writer do development system with the waterfall method and used unified model language system like use case diagram, activity diagram, class diagram, and flowchart diagram .The new system produce outputs featuring customer data, vendor data, product data, purchasing data, selling data and showing data that needed to ease Sumber Rejeki Jambi in processing data.